Lessons from 11 Country Case Studies : A Global Synthesis Report for the Global Conference on Universal Health Coverage for Inclusive and Sustainable Growth - World Bank (Washington, DC, 2014)
Several countries such as Japan, Brazil, Thailand and Turkey have achieved universal health coverage (UHC) and are proof of how UHC programs can serve as vital mechanisms for improving the health and welfare of the country's citizens. The UHC strives to ensure that no family is forced into poverty because of health care expenses, and that the gap in access to quality health services for the poorest forty percent of the population in every country is reduced and eventually eliminated. This document was created by the World Bank for presentation at the Global Conference on Universal Health Coverage for Inclusive and Sustainable Growth in December 2013 at Tokyo. It synthesizes findings from eleven country cases on UHC that were supported under the Japan-World Bank Partnership Program on Universal Health Coverage. the paper contains herein the objectives of the study, a framework for analysis, emerging lessons from country experiences, global lessons in the political economy and policy process, global lessons in health financing strategy, global lessons in health service delivery and human resources for health, lessons for countries in the four UHC groups, and a future course of action, interspersed with case studies from various countries.